Steam reforming of ethanol over electrically-heated anodic aluminum catalysts for hydrogen production. (21st September 2015) - Yao, Takami; Khanh Nguyen, Ha Thi; Mutamima, Anisa; Maki, Tei; Guo, Yu; Sakurai, Makoto; Kameyama, Hideo
Abstract: Technical development of fuel cell systems that are fueled by renewably produced bioethanol is required. In this research hydrogen is generated from a low-concentration ethanol solution using a steam reforming reaction and a nickel anodic-alumina catalyst (Ni/Al2 O3 ) with the Ni catalyst providing high selectivity of hydrogen at low cost. However, catalyst deactivation is known to occur because of oxidation of metallic Ni, sintering of Ni particles, and especially coke deposition as the significant problem. Adding Ce to Ni/Al2 O3 as a new co-catalyst reduces the amount of surface coke deposition, extending the durability of the catalyst, through the ability of Ce to store oxygen. In this work catalyst durability of more than 1022 h was achieved. Furthermore, this work has demonstrated catalyst durability can be increased. XRD analysis, EDS mapping and TPR analysis clarified the catalyst durability was improved because of the synergistic effect of a firmly fixed Ni layer connected to Ce on the catalyst surface. Highlights: We investigated relation between loading method of Ce and durability of Ni/Al2 O3 . DSS operating test confirmed that Ce-loaded Ni/Al2 O3 catalysts could be applied to residential fuel cell systems. Ni2Ce2 was found to have more than 1022 h in practical reformer conditions. The catalyst durability was improved because of the synergistic effect of Ni layer connected to Ce on the catalyst surface.